The role of Government in The Development of innovative activity in The Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2017)
The article describes the features of the development of the innovationprocess in Kazakhstan companies, made an analysis of the development of innovativeactivity in the Republic of Kazakhstan, formulated the main problemshindering the development of innovative entrepreneurship. Also in this paperwe consider the experience of foreign countries and organizations to supportinnovative activities, recommendations for the development of innovative strategiesfor the enterprise. Permanent and continuous creation and implementationof innovations is the main factor of succeeding in the competition of anyenterprise, region and country as a whole. Implementation of novelty, innovation,and new scientific and technological achievements in the production ofnew products, technologies and services is crucial for the development of thenational economy and raising the living standards of the population. In orderfor constantly improvement of welfare level, it is necessary to continuously improveand transform the products, services, improve production and managementfunctions on the basis of innovation and innovative technologies. Competitiveadvantage on the market now have countries that provide long-termstrategy of innovative development, aimed at various market needs.